Firm-Level Determinants of Export Performance in Kenya's Manufacturing Sector - Kimolo , Dorothy; Njaramba, Jennifer; Chesang', Laban (International Journal of Economics, 2024)
Purpose: This study aimed at investigating the firm-level determinants of export performance (export propensity and export intensity) in Kenya's manufacturing sector using firm-level panel data obtained from the World Bank Enterprise Surveys for the periods 2007, 2013 and 2018. Methodology: The study adopted a quantitative non-experimental research design. The Heckman Two-Stage estimation procedure was employed to jointly establish the firm-level determinants of export propensity and export intensity in Kenya's manufacturing sector. Findings: Based on the estimation results, firm-level total factor productivity, firm size, human capital, cost of material, electricity cost and foreign ownership had positive and significant effects on firms' export propensity while labor productivity negatively influenced export propensity. Firm age, capital intensity and research did not have significant effects on export propensity. On the other hand, export intensity was positively influenced by firm-level total factor productivity, foreign ownership, firm size, firm age, human capital and research. Labor productivity had a negative effect on firms' export intensity. Whereas the effect of energy cost on export intensity was weakly significant at 10 percent level of significance, there was no significant effect of cost of material on export intensity. Unique Contribution to Theory, Practice and Policy: Employing the new "˜new' trade theory, the study tested the self-selection hypothesis by analyzing the determinants of export propensity and intensity. According to the self-selection hypothesis, one of the key positive determinants of export propensity and export intensity is firm-level total factor productivity. The study findings validated the self-selection hypothesis since the results revealed firm-level total factor productivity as a positive and significant determinant of both export propensity and export intensity for Kenya's manufacturing firms. According to the study's conclusions, the government and enterprises must focus on policies that increase firm-level total factor productivity, firm size, human capital, and research in order to improve firms' export performance.